Neutrophil-to-lymphocyte ratio and chest x-ray severity in pediatric pulmonary tuberculosis: A cross-sectional analytic study - Muhammad As Alukal Lutfa; Muhammad Ricky Ramadhian; Wiwi Febriani; Retno Ariza Soeprihatini Soemarwoto (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Pulmonary tuberculosis (TB) remains a major health problem in children, particularly in low- and middle-income countries. Early assessment of disease severity is essential to guide clinical management. The neutrophil-to-lymphocyte ratio (NLR) has been proposed as a simple inflammatory biomarker that may reflect disease burden. However, evidence in pediatric TB remains limited. This study aimed to determine the association between NLR and chest X-ray (CXR) severity in pediatric patients with pulmonary TB aged 0–18 years. Methods: A cross-sectional analytic study was conducted at Dr. H. Abdul Moeloek Hospital, Bandar Lampung. Total sampling was applied, yielding 60 pediatric TB cases meeting inclusion and exclusion criteria. Secondary data were obtained from medical records, including baseline hematologic parameters and CXR severity classified as minimal, moderate, or extensive lesions. NLR values were categorized according to systemic inflammation levels. The Spearman correlation test was used to assess the association between NLR and CXR severity, with a significance threshold of p < 0.05. Results: Most participants were toddlers aged 1–<5 years (40%). More than half had normal NLR values (51.6%), and the most frequent CXR severity category was moderate lesions (53.3%). Correlation analysis demonstrated no significant association between NLR and CXR severity (r = –0.084, p = 0.524). These findings indicate that NLR does not correspond to radiological severity in pediatric TB. Conclusion: NLR appears unsuitable as a simple biomarker for predicting chest X-ray severity in pediatric pulmonary TB. Age-related immune immaturity and paucibacillary disease patterns in children may limit the utility of NLR in this population. Further studies with larger cohorts and additional inflammatory markers are recommended.